2004
DOI: 10.1254/jphs.fp0030565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mannitol on Ischemia-Induced Degeneration in Rat Hippocampus

Abstract: Abstract. Although mannitol has been used as an osmotherapeutic drug on brain injury, the clinical efficiency of the drug are still controversial. In the present study, we examined the effects of mannitol on the edema in a hippocampal slice due to brief ischemia. To evaluate the effects, we employed an image analysis system that consists of an infrared-differential interference contrast (IR-DIC) microscope, an infrared CCD camera, and a computer with custom-made software. By this system, severity of the edema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…7). The fluorescence intensity tended to increase even after ACSF reperfusion, which had been demonstrated previously by using a specific method (43,44). CsA and FK506 showed no significant protective effects on the morphological dynamics in cells and mitochondria.…”
Section: Effects Of Csa and Fk506 On Acute Toxicity Of L-glutamatesupporting
confidence: 66%
“…7). The fluorescence intensity tended to increase even after ACSF reperfusion, which had been demonstrated previously by using a specific method (43,44). CsA and FK506 showed no significant protective effects on the morphological dynamics in cells and mitochondria.…”
Section: Effects Of Csa and Fk506 On Acute Toxicity Of L-glutamatesupporting
confidence: 66%
“…32) Although mannitol cannot cross the blood brain barrier, it has a potent anti-edema action by drawing water from intracellular spaces into the intravascular space. 33) As a result, the brain has been thought to be rescued by lowering intracellular pressure, and thus by lowering intracranial pressure. Moreover, one of the nonosmotic mannitol effect is the protection against free radical-mediated ischemic cell damage.…”
Section: Disscusionmentioning
confidence: 99%
“…6,9,11,14,15) Various clinical and experimental investigations have shown that single doses of dexamethasone (DXM; exogenous glucocorticoids) or mannitol are extensively used in the treatment of cerebral ischemia and/or cerebral injury. [16][17][18] In the studies of heat stroke, pretreatment with DXM attenuated serum IL-1b levels and improved survival in heat stroke. 19) Additionally, pretreatment with mannitol before the onset of heat stroke caused significant reduction of the heat strokeinduced the increased free radical formation and intracranial hypertension.…”
mentioning
confidence: 99%